2006
DOI: 10.1002/mrm.21017
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of normal fetal brain maturation in utero by proton magnetic resonance spectroscopy

Abstract: The indications for fetal brain MRI have increased due to continuous improvements in MRI methods and instruments. As a matter of fact, MRI has become the method of choice to evaluate brain maturation and development (1,2), as well as abnormalities in those processes (1,3,4). The primary indications for fetal brain MRI are evaluations of central nervous system (CNS) malformations, ventricular dilatation, and pregnancies at risk of fetal brain damage (1,3-5). The classic MR protocol includes single-shot T 2 -wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 35 publications
5
76
0
5
Order By: Relevance
“…Linear regression analysis (least squares method) was used to fit a straight line with 95% confidence intervals (CIs) to the absolute metabolite concentrations and ratios as a function of GA. [28][29][30] The goodness of fit was assessed using the coefficient of determination (r 2 ) and the standard deviation of the residuals. The slope of the linear regression was tested at P Ͻ .05 as indicative of significance.…”
Section: Discussionmentioning
confidence: 99%
“…Linear regression analysis (least squares method) was used to fit a straight line with 95% confidence intervals (CIs) to the absolute metabolite concentrations and ratios as a function of GA. [28][29][30] The goodness of fit was assessed using the coefficient of determination (r 2 ) and the standard deviation of the residuals. The slope of the linear regression was tested at P Ͻ .05 as indicative of significance.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous MRS studies have not observed any detectable lactate peak in the brain of normal fetuses at any gestational age in the second half of pregnancy. 12 Nonetheless, we cannot exlude that lactate is present in the fetal brain at low and nonsignificant levels and may act as a fuel also in normal conditions. 37 Moreover, the time the MRS and the umbilical blood sampling can represent a potential limitation in making direct correlations between the 2 findings.…”
Section: Potential Limitationsmentioning
confidence: 94%
“…We located the VOI in the central brain areas (cerebral hemispheres; Figure 1), with the VOI centered on the midline to prevent any possible inclusion of scalp and extracranial tissues. To limit as much as possible any potential contamination from adjacent lipids during the acquisition of brain spectra, we ascertained whether the position of the fetal head was unchanged at the end of the 1 H MRS sequence by performing a rapid MRI (localizer) examination 12 to obtain spectra with a sufficient signal-to-noise ratio (SNR) in the shortest time possible.…”
Section: Fetal Localized Brain Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamate is produced by the fetal liver using maternal glutamine, and the excess of glutamate from the fetal circuit is removed by glutamate transporters (namely excitatory amino acid transporters: EAAT1, EAAT2 and EAAT3) in placenta (Battaglia, 2000;Noorlander et al, 2004). Glutamate is also the major excitatory neurotransmitter in the central nervous system of mammals and it is present in human fetal 4 brains at concentrations that did not vary during the third trimester of pregnancy (Girard et al, 2006). It mediates key aspects of normal brain function such as sensory information, motor coordination, emotions and cognition.…”
mentioning
confidence: 99%